Anatomy, function and regulation of neuropeptide EI (NEI) - Bittencourt, Jackson (2008)
This review is focused on the anatomy, role and behavior of neuropeptide-glutamic acid- isoleucine (NEI), providing a general report on the neuropeptide. In addition to hormone release, this peptide also takes part in the regulation of grooming behavior and locomotor activity. NEI is produced by cleavage of prepro-MCH that probably takes place at the Lys129-Arg130 and Arg145-Arg146 sites (the glycine residue on the C-terminus of NEI strongly suggests that this peptide is amidated). This same prohormone is also the precursor of MCH, widely studied in relation to food and water intake, and NGE, of which little is known. NEI and MCH are extensively colocalized throughout the central nervous system (CNS), and NEI is also present in peripheral tissues. The latter is also effective in stimulating luteinizing hormone (LH) release and, to a lesser extent, FSH from primary pituitary cell cultures. In addition to releasing LH from the medial eminence, NEI also acts directly on gonadotropes. Lastly, this neuropeptide also acts at the CNS level on gonadotropin-releasing hormone (GnRH) neurons.